Warta Ceria “Daud-goliat” - Juworo Bayu Kusumo (Institut Seni Indonesia Surakarta, 2020)
The work of Warta Ceria “Daud-Goliat” seeks an alternative media for children’s character education through performing arts. For this reason, an artwork that presents stories from the Bible was created by involving Sunday school children at the Javanese Christian Church, Pajang-Makamhaji. The concept of creating this work is Warta Ceria. This concept is inspired by Wayang Warta as a means of proclaiming stories from the Bible and refers to the learning system in Sunday schools that evokes a sense of joy in children. The methods used include: determining materials, collecting materials, processing materials, arranging materials, and packaging materials as an art show. The results obtained represent the creation of Warta Ceria “Daud-Goliat” in which children can learn and understand the message contained in the Bible story. Through the creative process, Sunday school children learn about Wayang Warta, acting, and dance movements that have encouraged them to build empathy, interaction, coordination, a sense of responsibility, and foster a sense of togetherness to support the children’s character building.